Myotonia may be a sign that prompts genetic testing for myotonic dystrophy type 1 - Eser, Metin; Hekimoğlu, Gulam; Kutlubay, Büşra (The European Research Journal, 2025)
Objectives: Myotonic dystrophy type 1 (DM1) is an autosomal dominant disorder characterized by myotonia, atrophy, and muscle weakness. Even though myotonic discharges can be shown on electromyography in DM1 instances, it is still difficult to distinguish DM1 clinically from other myotonic disorders. We aimed to examine the relationship between DM1 and myotonia. Methods: Data from 22 patients who had myotonia were analyzed retrospectively. Patients with DM1 (n=9) and non-DM1 myotonia (n=13) were categorized by genetic testing. Results: There was a significant difference in the incidence rates of myotonia (P=0.0001) between 8 out of 9 DM1 patients (89%) and 1 out of 13 non-DM1 (8%). Myotonic discharges were seen in 7 of the 9 DM1 (78%) patients. On the other hand, only 2 out of 13 (15%) patients with non-DM1 had myotonic discharges. There was a statistically significant difference in the incidence rates across the groups (P=0.003). In this study, we also encountered three siblings with DM1. We observed myotonia and muscle weakness in the twins, indicating there is a possibility of anticipation being seen in their grandchildren in the future. Conclusion: Genetic counseling is crucial for understanding disease variability, aiding in better DM1 management.